Modified Infant Feeding Tube as an Indigenous Endotracheal Tube in Unanticipated Congenital Subglottic Stenosis - Rahul Gupta; Rama Chatterjee; Neelam Dogra; Dinesh Kumar Barolia; Pratibha Rathore; Pooja Mongia (Faculty of Medicine-Universitas Airlangga, 2021)
Introduction: In neonates with an unanticipated difficult airway, there is an increased probability of failed intubation even with highly trained hands while performing direct laryngoscopy. Aims: We describe our experience of using a modified infant feeding tube (IFT) as an indigenous endotracheal tube (ETT) in a series of paediatric surgical patients with congenital subglottic stenosis (SGS). Material and Methods: A retrospective study was performed in our institute from January 2018 to December 2019. ETT with modified 6 and 8 French (Fr) sized IFT's were used. A stylet obtained from the VP shunt system was used to aid in intubation. Results: Out of 12,500 admissions in our department, there were 5 pediatric cases with SGS which were managed using modified IFT. Four were neonates and 1 infant (M:F = 2:3). Modified IFT(s) were used after failed intubation with ETT of size 2.5 mm in 4 patients (non-availability of ETT of size 2 mm), while in one neonate, even 2 mm ETT could not be negotiated due to SGS. In all the 5 children, successful intubation was finally performed with modified 8 French (Fr) IFT in 3, and with modified 6 Fr IFT in two cases. The surgical procedure was completed in 4 neonates out of 5 cases, while in one infant it was deferred due to the clinical condition of the patient and significant SGS. Conclusion: All 5 patients with SGS were managed without performing a tracheostomy. Modified IFT(s) is an effective alternative if smaller sized ETT(s) cannot be negotiated or unavailable in difficult neonatal and paediatric airway. This modified IFT as ETT has to be an important part of the emergency airway tray. It should not be considered as a replacement for routine use of standard ETT.